Donatist martyr stories : the Church in conflict in Roman North Africa - Tilley, Maureen A., 1948-; Tilley, Maureen A., 1948-; Tilley, Maureen A., 1948- (Translated texts for historians ;, 1996)
With this volume, Donatism regains its voice and its hagiography is available in English for the first time. The stories included provide a unique opportunity to glimpse the daily life of the church which for over a century was the faith of the majority of North African Christians. The narratives represent the lives and deaths of Christians who carried on pre-Constantine traditions from the fourth century to the advent of Islam.